Integrating enterprise information on demand with XQuery - Part 2.
In Part I of this article (XML-J, Vol. 4, issue 6), we introduced the enterprise information integration (EII) problem and explained how the XML query language XQuery and related technologies-specifically XML, XML Schema and Web services-are central to enabling this age-old problem to be successfully addressed at last.